Pregnancy Outcomes in Nurses and Nursing Assistants - Neranchana Sumsrisuwan; Kiattisak Kongwattanakul; Piyamas Saksiriwuttho (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To assess whether work as nurses and nursing assistants during pregnancy increases the risk of adverse pregnancy outcomes.Materials and methods: This study was prospectively carried out between June 2013 and August 2014. All nurses and nursing assistants who worked at Srinagarind Hospital during the study time frame were approached for recruitment. Data were collected by a self-administered questionnaire. Detailed information elicited from participants included baseline characteristics and underlying disease, occupational characteristics during pregnancy, and pregnancy outcomes. Logistic regression was used as a multivariate analysis to estimate an adjusted odds ratio (OR) and 95% confidence interval (CI) of factors associated with preterm delivery. Results: This study included 572 pregnancies occurring in 361 participants. Mean age at pregnancy was 29.1 years. Approximately 19.0% of pregnancies had underlying disease. Cesarean section rate was 29.3%. Preterm delivery was reported in 121 pregnancies, accounting for the rate of 21.1%. Pregnancies those complicated with underlying diseases and had rotating shift work carried a higher rate of preterm delivery (30.6% and 22.7%, respectively). Conclusion: The rate of self-reported preterm delivery among nurses and nursing assistants in this was approximately 20%. Preterm delivery trended to be more common among pregnancies those complicated by underlying diseases and had rotating shift work.